Unilateral Cozen's phenomenon from bilateral proximal tibial fractures a pediatric case study - Shrey S. Nihalani; Kevin A. Williams (Journal of Orthopaedic Reports)
Tibial fractures are common in children, with most occurring in the distal or midshaft regions. Younger children experience fractures from falls or torsion, while older children may fracture from direct impact or during sports. Treatment is based on individual factors and can include nonoperative methods or surgery. Complications such as angular deformity and compartment syndrome can arise. Cozen's Phenomena, a valgus deformity of the tibia, can occur with proximal tibia fractures but is rare in pre-pubertal children.The patient is a 7-year-old boy with no significant orthopedic history who suffered a left proximal metaphyseal tibia injury after falling from a trampoline. The patient's limb was successfully casted but developed recurvatum which eventually resolved with time. Eight months after the initial injury, the same patient presented with a right proximal metaphyseal tibia injury. The patient's injury healed with casting, but he began to develop valgus deformity of the tibia.Atraumatic injury with subsequent Cozen's phenomena in a prepubescent child is rare, and its etiology remains unknown. In the absence of significant risk factors, the presentation of this case highlights the curious nature of the phenomena.